The hero cults of Sparta: local religion in a Greek city - Pavlides, Nicolette A. (Bloomsbury classical studies monographs, 2023)
"This book examines the hero-cults of Sparta on the basis of the archaeological and literary sources. Nicolette Pavlides explores the local idiosyncrasies of a pan-Hellenic phenomenon, which itself can help us understand the place and function of heroes in Greek religion. Although it has long been noted that hero-cult was especially popular in Sparta, there is little known about the cults, both in terms of material evidence and the historical context for their popularity. The evidence from the cult of Helen and Menelaos at the Menelaion, the worship of Agamemnon and Alexandra/Kassandra, the Dioskouroi, and others who remain anonymous to us, is viewed as a local phenomenon reflective of the developing communal and social consciousness of the polis"--